Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/toxins13110766
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β Participates in Alternariol-Induced Oxidative Stress in Normal Prostate Epithelial Cells

Abstract: Alternaria toxins are considered as emerging mycotoxins, however their toxicity has not been fully evaluated in humans. Alternariol (AOH), the most prevalent Alternaria mycotoxin, was previously reported to be genotoxic and to affect hormonal balance in cells; however, its direct molecular mechanism is not known. The imbalance in androgen/estrogen ratio as well as chronic inflammation are postulated as factors in prostate diseases. The environmental agents affecting the hormonal balance might participate in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Here, using nontransformed intestinal cells, with the measurement of IL-8 secretion levels, we could demonstrate that both toxins can affect the proinflammatory response of IL-1β (5 h of incubation, Figure ). Even though the literature regarding ATX-II is limited, a recent study in hormone-sensitive prostate cells reported AOH to suppress IL-1β gene transcription . Furthermore, Kowalska and colleagues found AOH to induce IL-6 at transcript and protein levels, an effect that could be partially linked to the estrogen-like capacities of AOH toward the estrogen receptor β (ER-β) .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Here, using nontransformed intestinal cells, with the measurement of IL-8 secretion levels, we could demonstrate that both toxins can affect the proinflammatory response of IL-1β (5 h of incubation, Figure ). Even though the literature regarding ATX-II is limited, a recent study in hormone-sensitive prostate cells reported AOH to suppress IL-1β gene transcription . Furthermore, Kowalska and colleagues found AOH to induce IL-6 at transcript and protein levels, an effect that could be partially linked to the estrogen-like capacities of AOH toward the estrogen receptor β (ER-β) .…”
Section: Discussionmentioning
confidence: 88%
“…Besides, the toxin was found to suppress relative gene expression of the NF-κB subunit p65 (RelA), partly attributed to the endocrine capacity of AOH, in this particular in vitro model. 46 Supportive of the cross talk between AhR and Nrf2, CH-22, known as AhR antagonist, 33 showed the capability to suppress the Nrf2 nuclear/cytosol ratio for all substances tested ( Figure 5 ). On this note, it was recently reported for urolithin A (Uro A) that expression of both Nrf2 and AhR is crucial for the chemicals’ potential to increase mRNA levels of Nrf2 and heme oxygenase 1 (HO-1) in colon explants from mice.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Alternariol (AOH, Figure 1B), a small molecule produced by Alternaria alternata, is considered an "emerging mycotoxin", that requires toxicological risk assessment beyond its reported toxic effects (34,35). AOH was previously described to hold, amongst others, genotoxic, endocrine disruptive, pro-oxidative, and immunomodulatory potential (36)(37)(38)(39). Furthermore, AOH was suggested to impact cell membrane properties relevant for the innate immune response (40).…”
Section: Introductionmentioning
confidence: 99%